PENGEMBANGAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY UNTUK PENGGUNAAN ADOPSI MOBILE PAYMENT - Sani, Asrul; Pusparini, Nur Nawaningtyas; Budiyantara, Agus; Supit, Merliani Ivone (ISTEK WIDURI, 2023)
The retention of SMEs customers is of utmost importance for mobile payment service providers, particularly those who utilize mobile payments. Indonesia experienced a significant increase in the usage of mobile payment methods during the COVID-19 outbreak. Among the commonly utilized theoretical models in the Indonesian context of M-Payment payments, the Unified Theory of Acceptance and Use of Technology (UTAUT) model stands out. This proposed model is an expanded version of the UTAUT model, incorporating additional limited factors. It encompasses six variables that consider the diverse risks and costs perceived by users. The objective of this research is to analyze consumer behavior towards mobile payment systems using the UTAUT model and identify the determinants that consistently yield significant results. Data was successfully collected from 276 SMEs customers across various regions who utilize mobile payments through ShopeePay. The proposed model applies a minor segment structure using a regression seller model approach (SEM-PLS). The findings reveal that performance expectations, effort expectations, social influence, facilitation conditions, perceived risk, and perceived costs are the most influential predictors of users' intention to use the mobile payment system. Furthermore, behavioral intentions significantly influence actual usage behavior. The conclusion drawn from this research is that it enhances our understanding of the factors that determine the adoption of the mobile payment system, particularly in Indonesia.